A new species of bent-toed gecko (Cyrtodactylus, Gekkonidae) from the North Papuan Mountains - Oliver, Paul; Krey, Keliopas; _, Mumpuni; Richards, Stephen (Zootaxa, 2011)
We describe a new species of Cyrtodactylus from lower montane forests on the Torricelli and Foja Mountain ranges of northern New Guinea. Cyrtodactylus boreoclivus sp. nov. can be distinguished from all other described Cyrtodactylus by the combination of moderately large size (SVL 104–109 mm), males with pores extending to the knee and arranged in independent precloacal and femoral series, transversely enlarged subcaudal scales, and dorsal pattern consisting of five to seven indistinct transverse dark bands. The known distribution of this species is similar to many other vertebrate taxa apparently restricted to isolated ranges within the North Papuan Mountains, and supports the biogeographic association of these poorly known upland areas.